Implementation of the Circumstantial Evidence in the Evidence Mechanism Process on Cartel Cases in Indonesia - Supriatna, Rimba; Siska, Frency; Dzulhijjah, Liza (KnE Social Sciences, 2023)
Proving a cartel as one of the agreements prohibited in Law Number 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition is not easy. Therefore, KPPU often uses indirect evidence as evidence in giving its decision, but this indirect evidence is not yet known in the legal system in Indonesia. This study aims to analyze the implementation of the use of indirect evidence in the process of proving cartel cases in Indonesia. The results of this study indicate that the implementation of the use of indirect evidence in the process of proving cartel cases in Indonesia has not been effective because it collides with the procedural law system in Indonesia, which has not accommodated indirect evidence so that many KPPU decisions have been cancelled both at the level of objection and cassation. Keywords: evidence indirect evidence, business competition